Sovereign Debt Management in Crisis in Europe and Central Asia : A Toolkit for Policy Maker - World Bank (Washington, DC, 2016)
The global financial crisis of 2008-2009 required most sovereign debt managers to adapt to rapidly changing market circumstances, by changing the mix of borrowing instruments and adopting techniques that minimize the impact of severe market dislocations and increased risk aversion. These actions, allied to prudent macroeconomic and debt management policies implemented by government in the years preceding the crises, were critical in helping countries meet their financing needs without undue strain on the financial markets. This toolkit draws on the approaches taken by a range of countries and provides sovereign debt policy makers with a rich set of potential actions to address crisis periods. A practical illustration on the use of some of these actions is conducted by analyzing the measures taken by Romania, Serbia and Turkey as a response to the recent crises. Authors draw lessons from these experiences and examine what other measures included in the toolkit could have been used to boost the crisis response impact in these economies, respecting country-specific contexts.